3
$\begingroup$

In Fraleigh, there is what appears to be a classic theorem on cosets. I'm confused about the proof for the converse.

Theorem. Let $H$ be a subgroup of a group $G$. Then left coset multiplication is well defined by the equation $$(aH)(bH) = (ab)H$$ if and only if $H$ is a normal subgroup of $G$.

Proof. ...We now turn to the converse: if $H$ is a normal subgroup, then left multiplication by representatives is well-defined. Suppose we wish to compute $(aH)(bH)$. Choosing $a \in aH$ and $b \in bH$, we obtain the coset $(ab)H$. Choosing different representatives $ah_1 \in aH$ and $bh_2 \in H$, we obtain the coset $ah_1 b h_2 H$. We must show these are the same coset. Now $h_1 b \in H b = bH$, so $h_1b = bh_3$ for some $h_3 \in H$. Thus $$(ah_1)(bh_2) = a(h_1 b) h_2 = a(bh_3)h_2 = (ab)(h_3h_2)$$ and $(ab)(h_3h_2) \in (ab)H.$ Therefore $ah_1 b h_2$ is in $(ab)H$.

This seems weird to me. Why do we name our second representatives $ah_1$ and $bh_2$, rather than $a', b' \in G$? For example, in this post Arturo produces a proof for this,

Proof. Suppose $H$ is normal. Then $gH=Hg$ for every $g\in G$. If $xH=x'H$ and $yH=y'H$, then $$xyH = x(yH) = x(Hy) = x(Hy') = (xH)y' = > (x'H)y' = x'(Hy') = x'(y'H) = x'y'H$$ so the operation is well defined.

There must be some motivation for using this seemingly awkward way of picking representatives.

$\endgroup$
3
$\begingroup$

This difference probably just arises as a result of different expositional choices by the authors about "cosets," but at any rate both explanations work.

If Fraleigh defines $aH=\{ag\mid g\in H\}$, then his description makes sense, because that's the only description you have of $aH$.

Arturo on the other hand might choose to present $aH$ to be the equivalence class of things under the relation $x\sim y\iff x^{-1}y\in H$. In that case, when Arturo writes $aH=bH$, we implicitly have $b=a(a^{-1}b)=ah$.

While Arturo's expression is more compact, Fraleigh's notation does have one benefit. Some beginners mistakenly believe that $aH=Ha$ means that $ah=ha$ for all $h\in H$. By going down to the level of $h_i$'s in his notation, Fraleigh is clear that no such commutation is taking place:

$$(ah_1)(bh_2) = a\underline{(h_1 b)} h_2 = a\underline{(bh_3)}h_2 = (ab)(h_3h_2)$$

With the "simplified" notation, beginners might overlook that detail.

$\endgroup$
2
$\begingroup$

Remember, too, that $aH =\{ah:h\in H\}$. So his first choice of representatives weren't just $a$ and $b$, they really were of the form $ah'_1$ and $bh'_2$ (take $h'_1 = h'_2 =e$) like the second choice of representatives $ah_1$ and $bh_2$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.